Angiogenesis precedes cardiomyocyte migration in regenerating mammalian hearts - Ingason, Arnar B. (J Thorac Cardiovasc Surg, 2017)
OBJECTIVE: Although the mammalian heart's ability to fully regenerate is debated, its potential to extensively repair itself is gaining support. We hypothesized that heart regeneration relies on rapid angiogenesis to support myocardial regrowth and sought to characterize the timeline for angiogenesis and cell proliferation in regeneration. METHODS: One-day-old CD-1 mice (P1, N =14; 60) underwent apical resection or sham surgery. Hearts were explanted at serial time points from 0 to 30 days post-resection and analyzed with immunohistochemistry to visualize vessel ingrowth and cardiomyocyte migration into the resected region. Proliferating cells were labeled with 5-ethynyl-2′-deoxyuridine injections 12 hours before explant. 5-Ethynyl-2′-deoxyuridine–positive cells were counted in both the apex and remote areas of the heart. Masson's trichrome was used to assess fibrosis. RESULTS: By 30 days postresection, hearts regenerated with minimal fibrosis. Compared with sham surgery, apical resection stimulated a significant increase in proliferation of preexisting cardiomyocytes between 3 and 11 days after injury. Capillary migration into the apical thrombus was detected as early as 2 days postresection, with development of mature arteries by 5 days postresection. New vessels became perfused by 5 days postresection as evidenced by lectin injection. Vessel density and diameter significantly increased within the resected area over 21 days, and vessel ingrowth always preceded cardiomyocyte migration, with coalignment of most migrating cardiomyocytes with ingrowing vessels. CONCLUSIONS: Endothelial cells migrate into the apical thrombus early after resection, develop into functional arteries, and precede cardiomyocyte ingrowth during mammalian heart regeneration. This endogenous neonatal response emphasizes the importance of expeditious angiogenesis required for neomyogenesis.